2012
DOI: 10.5296/ijhrs.v2i1.1242
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Organizational Learning Capability and Job Satisfaction

Abstract: The effectiveness and productivity of an organization depends on its staff and if they don't be satisfied from their job, continues of living for such organization is impossible. One of the important factors which influence on job satisfaction, is an organizational learning capability (OLC). So, the purpose of this paper is to analyze the relationship between organizational learning capability and its dimensions (experimentation, risk taking, interaction with the external environment, dialogue and participativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…This study also indicated that organizational learning has a significant positive effect on job satisfaction and it was supported by several previous studies (Egan et al, 2004;Jolodar & Jolodar, 2012;Razali et al, 2013;Rose, Kumar, & Pak, 2005). Rowden and Conine (2005) investigated the effect of organizational learning on job satisfaction and found a significant positive relationship between both variables.…”
Section: International Journal Of Human Resource Studiessupporting
confidence: 88%
See 2 more Smart Citations
“…This study also indicated that organizational learning has a significant positive effect on job satisfaction and it was supported by several previous studies (Egan et al, 2004;Jolodar & Jolodar, 2012;Razali et al, 2013;Rose, Kumar, & Pak, 2005). Rowden and Conine (2005) investigated the effect of organizational learning on job satisfaction and found a significant positive relationship between both variables.…”
Section: International Journal Of Human Resource Studiessupporting
confidence: 88%
“…Previous researches reported that organizational learning is associated with job satisfaction (Egan, Yang, & Bartlett, 2004;Emami et al, 2012;Jolodar & Jolodar, 2012;Razali et al, 2013). Chang and Lee (2007) revealed that the promotion of organizational learning can increase job satisfaction.…”
Section: Organizational Learningmentioning
confidence: 98%
See 1 more Smart Citation
“…The study was on information technology (IT) employees in the United States. Another study conducted by Jolodar & Jolodar (2012) concluded that there is a positive relationship between organizational learning and job satisfaction. It was also discovered that organizational leaning was positively influenced by job satisfaction, a study among academic staff in a private university in Malaysia by Moradi, Almutairi, Idrus and Emami (2013).…”
Section: Organizational Learningmentioning
confidence: 99%
“…Job satisfaction among employees and workforce is a crucial element of organizational success especially in managing the human resources of the organization (Zahari et al, 2020;Gitoho, 2015). There are a few factors that can affect job satisfaction for instance, Jolodar and Jolodar (2012) proved that job satisfaction was related with employee productivity and human resources development. Based on a study conducted by (Lo & Ramayah, 2011) there are several elements that linked to job satisfaction.…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%